Colorectal cancer specific conditions promote Streptococcus gallolyticus gut colonization - Aymeric, Laetitia (Proc Natl Acad Sci U S A, 2018)
Colonization by Streptococcus gallolyticus subsp. gallolyticus (SGG) is strongly associated with the occurrence of colorectal cancer (CRC). However, the factors leading to its successful colonization are unknown, and whether SGG influences the oncogenic process or benefits from the tumor-prone environment to prevail remains an open question. Here, we elucidate crucial steps that explain how CRC favors SGG colonization. By using mice genetically prone to CRC, we show that SGG colonization is 1,000-fold higher in tumor-bearing mice than in normal mice. This selective advantage occurs at the expense of resident intestinal enterococci. An SGG-specific locus encoding a bacteriocin (“gallocin”) is shown to kill enterococci in vitro. Importantly, bile acids strongly enhance this bacteriocin activity in vivo, leading to greater SGG colonization. Constitutive activation of the Wnt pathway, one of the earliest signaling alterations in CRC, and the decreased expression of the bile acid apical transporter gene Slc10A2, as an effect of the Apc founding mutation, may thereby sustain intestinal colonization by SGG. We conclude that CRC-specific conditions promote SGG colonization of the gut by replacing commensal enterococci in their niche.